Reducing Application-level Checkpoint File Sizes: Towards Scalable Fault Tolerance Solutions - Cores, I.; Rodriguez, G.; Martin, M. J.; Gonz'lez, P. (2012 IEEE 10th International Symposium on Parallel and Distributed Processing with Applications, 2012)
Systems intended for the execution of long-running parallel applications require fault tolerant capabilities, since the probability of failure increases with the execution time and the number of nodes. Checkpointing and rollback recovery is one of the most popular techniques to provide fault tolerance support. However, in order to be useful for large scale systems, current checkpoint-recovery techniques should tackle the problem of reducing checkpointing cost. This paper addresses this issue through the reduction of the checkpoint file sizes. Different solutions to reduce the size of the checkpoints generated at application level are proposed and implemented in a checkpointing tool. Detailed experimental results on two multicore clusters show the effectiveness of the proposed methods.